Recognition and enforcement of foreign arbitral awards: a global commentary on the New York Convention - Kronke, Herbert (Kluwer Law, 2024)
About the Contributors --Foreword --Preface and Acknowledgments --A Note on Citations --List of Abbreviations --Introduction The New York Convention Fifty Years on: Overview and Assessment --Article I --Article II --Article III --Article IV --Article V(1)(a) --Article V(1)(b) --Article V(1)(c) --Article V(1)(d) --Article V(1)(e) --Article V(2) --Article VI --Article VII --Article VIII --Article IX --Article X --Article XI --Article XII --Article XIII --Article XIV --Article XV --Article XVI --Convention on the Recognition and Enforcement of Foreign Arbitral Awards (New York Convention, 1958) --Recommendation Regarding the Interpretation of Article II, Paragraph 2, and Article VII, Paragraph 1, of the Convention on the Recognition and Enforcement of Foreign Arbitral Awards --Convention on the Execution of Foreign Arbitral Awards (Geneva Convention, 1927) --Protocol on Arbitration Clauses (Geneva Protocol, 1923) --References.
Commentary in honour of the 50. anniversary of the Convention
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards -- (1958); Kommentar; Internationale Schiedsgerichtsbarkeit